CREATING THE IMAGE OF THE UNIVERSITY - Szwacka-Mokrzycka, Joanna; Abutalibov, Rasim (Acta Scientiarum Polonorum. Oeconomia, 2014)
The main objective of this study is to present the impact of the Erasmus student exchange programme on the university image building. The first part of the paper, describes forms of promotion which are most commonly used by universities, namely: advertising, sponsorship, personal selling, online promotion and engagement marketing. The impact of the Erasmus programme on the university image building is exemplified by the Warsaw University of Life Sciences - SGGW. The paper presents the history, the strengths and the promotional potential of the SGGW. In addition, the paper offers results of a survey, conducted among grantees participating in the Erasmus programme, which aimed at examining the familiarity and effectiveness of applied forms of promotion.